(untitled) (DAPesquisa, 2020)
This study exposes one of the results of a research on verbal and non-verbal significance developed through theatrical practice developed in my Master course, based on the observation of the relatioship between language, body and cognition with aphasic people. I investigate the multimodal co-occurrence of semiosis (speech, gesture, body expression, gaze, etc.) with aphasic people, through the interactions of different, yet shared, semiotic processes, active in the construction of meanings, to describe and analyze the role of performative artistic activity in the (re)organization of communicative and expressive possibilities of aphasic individuals in the world and with their peers.